Complex strength performance in patients with haemophilia A - Runkel, B.; Kappelhoff, M.; Hilberg, T. (Hämostaseologie, 2015)
The aim of this study was to develop a complex strength measurement method and to apply this new method for the first time in patients with haemophilia (PwH). 20 PwH with severe haemophilia A and 20 controls were included into the study. All subjects completed ten measurements of maximum isometric strength. Furthermore, the 20 control subjects completed re-test-measurements to evaluate the method.As a result, the method showed a high reliability (ICC 0.764 to 0.934). Between the two groups significant reductions in PwH between –(19–35%) were detected, regarding the relative force of the M. triceps brachii (–19%; p = 0.008), M. biceps brachii (–19%; p = 0.031), M. latissimus dorsi (–17%; p = 0.019), M. biceps femoris right (–20%; p = 0.036) and M. quadriceps femoris (right: –29%; p = 0.004; left: –35%; p = 0.002). No differences were found for M. rectus abdominis and in the hand strength. Thus, there is no general deficit in the muscle strength in PwH. The most obvious deficits exist in the upper and lower extremities and in the back muscles.PwH should carry out complex muscle strength training and integrate it early into a comprehensive treatment concept.
Keywords: Haemophilia; strength; method development; testing